Single-cell RNA-sequencing and microarray analyses to explore the pathological mechanisms of chronic thromboembolic pulmonary hypertension - Miao, Ran; Dong, Xingbei; Gong, Juanni; Li, Yidan; Guo, Xiaojuan; Wang, Jianfeng; Huang, Qiang; Wang, Ying; Li, Jifeng; Yang, Suqiao; Kuang, Tuguang; Liu, Min; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objective The present study aimed to explore the pathological mechanisms of chronic thromboembolic pulmonary hypertension (CTEPH) using a gene chip array and single-cell RNA-sequencing (scRNA-seq). Materials and methods The mRNA expression profile GSE130391 was downloaded from the Gene Expression Omnibus database. The peripheral blood samples of five CTEPH patients and five healthy controls were used to prepare the Affymetrix microRNA (miRNA) chip and the Agilent circular RNA (circRNA) chip. The pulmonary endarterectomized tissues from five CTEPH patients were analyzed by scRNA-seq. Cells were clustered and annotated, followed by the identification of highly expressed genes. The gene chip data were used to identify disease-related mRNAs and differentially expressed miRNAs and circRNAs. The protein–protein interaction (PPI) network and the circRNA–miRNA–mRNA network were constructed for each cell type. Results A total of 11 cell types were identified. Intersection analysis of highly expressed genes in each cell type and differentially expressed mRNAs were performed to obtain disease-related genes in each cell type. TP53, ICAM1, APP, ITGB2, MYC, and ZYX showed the highest degree of connectivity in the PPI network of different types of cells. In addition, the circRNA–miRNA–mRNA network for each cell type was constructed. Conclusion For the first time, the key mRNAs, miRNAs, and circRNAs, as well as their possible regulatory relationships, during the progression of CTEPH were analyzed using both gene chip and scRNA-seq data. These findings may contribute to a better understanding of the pathological mechanisms of CTEPH.